Z(2)-FET as Capacitor-Less eDRAM Cell For High-Density Integration - Navarro, Carlos; Duan, Meng; Parihar, Mukta Singh; Adamu-Lema, Fikru; Coseman, Stefan; Lacord, Joris; Lee, Kyunghwa; Sampedro, Carlos; Cheng, Binjie; El Dirani, Hassan; Barbe, Jean-Charles; Fonteneau, Pascal; et al. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
2-D numerical simulations are used to demonstrate the Z(2)-FET as a competitive embedded capacitor-less dynamic random access memory cell for low-power applications. Experimental results in 28-nm fully depleted-silicon on insulator technology are used to validate the simulations prior to downscaling tests. Default scaling, without any structure optimization, and enhanced scaling scenarios are considered before comparing the bit cell area consumption and integration density with other eDRAM cells in the literature.
Keywords: OPERATION; 1T-DRAM